Mysteries of Lisbon: Story and Structure - Marshall Deutelbaum (Aniki: Revista Portuguesa da Imagem em Movimento, 2014)
This essay analyzes the structure of Mysteries of Lisbon by reconstructing its story in chronological sequence and by examining how in place of the single character striving to achieve a goal or solve a puzzle as one would expect to discover at the heart of the typical classical Hollywood film, Mysteries of Lisbon employs an unusual, echoing structure between the film’s two parts that tightly interrelates the actions of multiple characters who appear otherwise to be related merely by apparent coincidence.